(3CSGS GdHdGZIs - (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3Ydi Hf eMeO Hf GdMSf GdedbH HGdbhGe s)
(3ChdgG (B:s
(3GKfGA HGH GdOGd hLGAfG hYdjg OGMI , hbGd CHh MeRI GdUhai (B: (3dhdG MHJi OGMg dcGf GdehJ di QGMI abjd dg (B: (3heG GdOGMg ? bGd GdOfjG hef GdeLGR (B: (3adGf ef OhMI GdcQe s
(3eged GdfbW CMjGfGs
(3JJab ai BNQgG BNQ GdfSNI GdKGdKIs
(3fSNI QGHYIs
(3HgGBKGQ JbWjY GdeJMa GdYQGbi HZOGO (B615s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GddZIs